QUO VADIS PENGAJARAN ILMU EKONOMI? - Bagus Santoso (Faculty of Economics and Business, Universitas Gadjah Mada, 2002)
This paper examines the teaching curriculum at the Faculty of Economics Gadjah Mada University and its future development. Better quality of teaching materials on quantitative as well as qualitative methods should be the final goal. Recently there were “talks” among faculty members to change the name of the faculty of economics to became Faculty of Economics and Business. This paper argues against the idea.Keywords: Neoclassical and Keynesian Economics, Economics Teaching.